PEMBERDAYAAN USAHA KONVEKSI DAN PENGENALAN AKSES KE PEMBIAYAAN SYARIAH DI DESA GUNUNG BUNDER II, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Tasya Audina Oktavia; Rully Trihantana; Miftakhul Anwar (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
The purpose of this service is to prevent the transmission of the COVID-19 virus and convection business empowerment to residents who will take part in posyandu activities in Gunung Bunder II village by distributing cloth masks and providing hand sanitizer. The method of implementing this activity begins with distributing cloth masks to residents who come to the posyandu who do not use masks, then giving directions to implement health rules for residents who come to the posyandu to avoid the virus. From this activity, it is hoped that the use of cloth masks and hand sanitizers as well as directives and guidance on COVID-19 can break the chain of transmission of COVID-19 and increase public awareness and vigilance against the COVID-19 virus by training them to get used to implementing health protocols. Keywords: Empowerment of Confection Business, Implementation of Health Protocol, Posyandu